Analisis Semiotik Dalam Lirik Lagu “Amin Paling Serius” Karya Sal Priadi & Nadin Amizah - Indriyani, Dewi; Diana, Ani; Saputry, Dessy (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Research uses the lyrics of the song "Amin Paling Serius" by Sal Priadi and Nadin Amizah. Aims to find out the signifiers and signifieds in song lyrics using Ferdinand De Sausurre's semiotic theory based on the object system of signifiers and signifieds. This research uses a descriptive qualitative method, by reading and taking notes to find out the system of signs contained in the lyrics of the song "Amin Paling Serius" by Sal Priadi and Nadin Amizah. Based on the results of the analysis based on the system of signs in the lyrics of the song "Amin Paling Serius" by Sal Priadi and Nadin Amizah, there are signs and signifiers that point to romance. Where in it there is an ideal form of harmony. This form of love has three components, namely passion, intimacy and commitment. This is an ideal form of true love.